SERCA Overexpression Improves Mitochondrial Quality Control and Attenuates Cardiac Microvascular Ischemia-Reperfusion Injury - Ying Tan; David Mui; Sam Toan; Pingjun Zhu; Ruibing Li; Hao Zhou (Elsevier, 2020)
Despite significant advances in the treatment of myocardial ischemia-reperfusion (I/R) injury, coronary circulation is a so far neglected target of cardioprotection. In this study, we investigated the molecular mechanisms underlying I/R injury to cardiac microcirculation. Using gene delivery, we analyzed microvascular protective effects of sarcoplasmic/endoplasmic reticulum Ca2+-ATPase (SERCA) on the reperfused heart and examined the role of SERCA in regulating mitochondrial quality control in cardiac microvascular endothelial cells (CMECs). Our data showed that SERCA overexpression attenuates lumen stenosis, inhibits microthrombus formation, reduces inflammation response, and improves endothelium-dependent vascular relaxation. In vitro experiments demonstrated that SERCA overexpression improves endothelial viability, barrier integrity, and cytoskeleton assembly in CMECs. Mitochondrial quality control, including mitochondrial fusion, mitophagy, bioenergetics, and biogenesis, were disrupted by I/R injury but were restored by SERCA overexpression. SERCA overexpression also restored mitochondrial quality control by inhibiting calcium overload, inactivating xanthine oxidase (XO), and reducing intracellular/mitochondrial reactive oxygen species (ROS). Administration of exogenous XO or a calcium channel agonist abolished the protective effects of SERCA overexpression on mitochondrial quality control and offset the beneficial effects of SERCA overexpression after cardiac microvascular I/R injury. These findings indicate that SERCA overexpression may be an effective approach to targeting cardiac microvascular I/R injury by regulating calcium/XO/ROS signaling and preserving mitochondrial quality control.